KEMAMPUAN REPRESENTASI MATEMATIS DITINJAU DARI GAYA BELAJAR SISWA SMA DI KOTA CIREBON DALAM MENYELESAIKAN MASALAH SPLDV dan SPtLDV - Nur Komalasari; Sri Winarsih; Anggita Maharani; Muchamad Subali Noto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This study aims to analyze the characteristics of students with visual, auditory and kinesthetic learning styles in solving SPLDV and SPtLDV problems. The research method taken is a qualitative research method. Qualitative research is carried out by means of observation, interviews, or document review. The results of this study are the characteristics of thirty-six students obtained that students who have symbolic representation skills are twelve students (33.33%) with five students (13.89%) having a kinesthetic learning style, three students (8.33%) having an auditory learning style, and four students (11.11%) having a visual learning style. Then students who had verbal representation skills were ten students (27.78%) with four students (11.11%) having a kinesthetic learning style, five students (13.89%) having an auditory learning style, and one student (2.78%) having a visual learning style. The students who had visual representation skills were fourteen students (38.89%) with four students (11.11%) having a kinesthetic learning style, one student (2.78%) having an auditory learning style, and nine students (25%) having a visual learning style.